KONSELING ADLERIAN INTEGRATIF ISLAM: MENYATUKAN SPIRITUALITAS DAN PSIKOLOGI SOSIAL DALAM PEMBENTUKAN KEPRIBADIAN SEHAT - Muhammad Aulia Aulia; Fatheni Cova Kamil Khairy; Masril (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The development of modern counseling theory demonstrates the need for an integrative approach that unites psychological, social, and spiritual dimensions in the formation of a healthy personality. This study aims to formulate a conceptual model of Islamic Integrative Adlerian Counseling, a theoretical framework that combines Alfred Adler’s principles of Individual Psychology with Islamic spirituality. The research employs a qualitative approach using a library research design, through systematic analysis of national and international scholarly sources. The findings indicate that core Adlerian values such as social interest, goal orientation, and the creative self have epistemological compatibility with Islamic teachings, particularly the concepts of tazkiyah al-nafs (purification of the self), ihsan (excellence in conduct), and ukhuwah insaniyah (human brotherhood). The integration of these elements produces a holistic counseling model oriented toward spiritual and social balance, utilizing techniques such as encouragement, muhasabah (self-reflection), and reflection on life’s meaning. Theoretically, this model enriches interdisciplinary studies between Western psychology and Islamic scholarship, while practically, it holds potential as an alternative contextual counseling approach for educational institutions and Muslim communities. These findings affirm the urgency of developing an integrative counseling paradigm aligned with divine and human values in fostering healthy personality development in the modern era.